Isolation of lignin from oil palm empty fruit bunch (OPEFB) by using organosolv method - Nor Nadiah, Mohamad (2015)
This research focus on the isolation of lignin component from lignocellulosic biomass of oil palm empty fruit bunch (OPEFB) using the organosolv method. Lignin has a unique structure where it consist of varies aromatic compound in their polymeric chain lignin that capable to copolymerize alternative units that derive from incomplete monolignol biosynthesis in plants. Nowadays, trending in lignin research was to focus the integration into lignin polymer and also improve the lignin degradation. Among the pretreatment methods to isolate lignin from its lignocellulosic biomass, the organosolv method process is the promising pretreatment method for biorefinery approach. Common organosolv methods consist of cooking lignocellulosic biomass in aqueous ethanol solvent at high temperature and carry out in a pressurized reactor. However, in this study, modification on organosolv method has been made where this reaction was carry out by refluxing at ambient pressure and lower temperature. Two parameters have been studied during the process: i) Extraction times (4-8 hour) ii) Ethanol concentrations (65-75% vol.). From the results, extraction time and ethanol concentration gives large effects to delignification. While delignification is decreased by lower extraction time and higher solvent concentration, pulp yield increased and thus decreased the yield of lignin. Extension of time leads to a decrease of the pulp yield and increase the lignin yield. For overall ethanol concentration, it can be shown that there is no significant effect in their trend. Mostly, the highest lignin yield was recorded at extraction time of 8 hour with 6.73% lignin yield (65% ethanol vol.), 8.91% lignin yield (70% ethanol vol.). However, for 75% ethanol vol., the highest was at 6 hour with 5.44% lignin yield. For solvent concentration effect, overall maximum lignin yield was observed at 70% ethanol. The highest lignin yield isolated at maximum extraction time (8 hour) was at 70% ethanol concentration with 8.91% lignin yield followed by 65% with 6.73% and 75% at 4.66% only. From this trend, it can be shown that a further increase ethanol concentration at 70% vol. reduces the lignin yield. Solvent concentration and extraction time gives an intense impact to this process as these parameters able to lead to much economical process condition to isolate high yield of lignin.